Catalytic cracking of coal-tar model compounds over ZrO2/Al2O3 and Ni-Ce/Al2O3 catalysts under steam atmosphere. (1st March 2020) - Zhong, Mei; Zhai, Jianrong; Xu, Yuebing; Jin, Lijun; Ye, Yufang; Hu, Haoquan; Ma, Fengyun; Fan, Xing
Highlights: ZrAlO solid solution with a new pore framework is formed in prepared ZrO2 /Al2 O3 . ZrO2 /Al2 O3 catalyst enhances the cracking efficiency of pyrene. Higher content of Zr leads to the deep cracking of pyrene to form carbon. Naphthalene is mainly generated from catalytic cracking of pyrene over Ni-Ce/Al2 O3 . Abstract: A series of mesoporous ZrO2 /Al2 O3 and Ni-Ce/Al2 O3 catalysts were prepared using mechanochemical method and characterized by XRD, N2 adsorption, NH3 -TPD, O2 -TPD and XPS. Catalytic cracking of toluene/pyrene, a model compound of coal tar, was investigated under steam atmosphere in a fixed-bed reactor where ZrO2 /Al2 O3 and Ni-Ce/Al2 O3 catalysts were sequentially layered. The results show that ZrAlO solid solution with a new pore framework is formed in prepared ZrO2 /Al2 O3 catalysts, resulting in higher BET surface area, larger pore volume and more adsorption sites than pure ZrO2 and Al2 O3 . Meanwhile, the formation of ZrAlO inhibits the transformation of tetragonal ZrO2 to monoclinic ZrO2 and obviously generates strong acid sites. The use of ZrO2 /Al2 O3 catalyst increases cracking efficiency of pyrene due to promoting active hydrogen formation from H2 O and converting pyrene to monocyclic, dicyclic and tricyclic aromatics, which can be further decomposed by Ni-Ce/Al2 O3 catalysts to form naphthalene. ZrO2 /Al2 O3 with a certain amount of Zr favors the cracking of pyrene and inhibits total yield of carbon deposition. When Zr content exceeds 50 wt%, a deep cracking of pyrene occurs, resulting in serious carbon deposition and decrease in liquid and naphthalene yields. The cracking of toluene and pyrene contribute to the formation of naphthalene, whereof, the latter is the primary way. Different distribution of liquid products for cracking of either toluene or toluene/pyrene was observed over ZrO2 /Al2 O3 and Ni-Ce/Al2 O3, respectively. It was also demonstrates that the carbon formed on the spent ZrO2 /Al2 O3 catalysts is amorphous, whereas that deposited on the spent Ni-Ce/Al2 O3 is carbon filaments.